2010
DOI: 10.1590/s1516-35982010000600016
|View full text |Cite
|
Sign up to set email alerts
|

Forma física, suplementação enzimática e nível nutricional de rações para frangos de corte na fase inicial: desempenho e digestibilidade dos nutrientes

Abstract: RESUMO -Foram conduzidos dois experimentos, utilizando um total de 1.440 frangos de corte machos de 8 a 21 dias de idade, para avaliar a forma física da ração, o uso de enzimas e os níveis nutricionais em dietas à base de milho e farelo de soja. Foi adotado delineamento inteiramente casualizado, em esquema fatorial 2 × 2 × 2, com duas formas físicas de ração (farelada ou triturada); sem ou com complexo enzimático (amilase, celulase e protease) e dois níveis nutricionais (95 ou 100% das recomendações). No exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…According to Pucci et al (2010), the cause of the lower consumption of micropelleted food is due to the glycostatic factor, where the food receives high temperatures during its production, which facilitates starch digestibility. There is also the breakdown of some organelles, making carbohydrates and proteins more palatable for birds.…”
Section: Resultsmentioning
confidence: 99%
“…According to Pucci et al (2010), the cause of the lower consumption of micropelleted food is due to the glycostatic factor, where the food receives high temperatures during its production, which facilitates starch digestibility. There is also the breakdown of some organelles, making carbohydrates and proteins more palatable for birds.…”
Section: Resultsmentioning
confidence: 99%
“…Those authors suggest that by adopting additional supply, an inclusion method used for Enzyme Blend, differences can be reduced, consequently reducing the likelihood of significant differences. Other authors, however, observed an improvement (p<0.05) in the feed conversion of broilers fed corn and soybean mealbased diets supplemented with an enzyme complex under the same inclusion method (Pucci et al, 2010).…”
Section: Factormentioning
confidence: 92%
“…However, Pucci et al (2010) showed that supplemented EC mixture (amylase, cellulase and protease) to broilers diets based on corn and soybean meal significantly (P<0.05) improved FCR. Angel et al (2011) reported that the as-similation of nutrients by the birds especially in the early stage of life improved by supplementation of endogenous enzyme production which in turn improves as a result of the addition of exogenous enzymes.…”
Section: Experiments Two (Exp2)mentioning
confidence: 92%